1996
DOI: 10.1080/095530096146147
|View full text |Cite
|
Sign up to set email alerts
|

Free radical mechanism for the effects of environmental electromagnetic fields on biological systems

Abstract: The radical pair mechanism is discussed as a possible route whereby a magnetic field of environmental strength might affect a biological system. It is well established as the origin of reproducible field effects in chemistry, and these can be observed even at very low magnetic field strengths, including that of the geomagnetic field. Here it is attempted to give a description which might assist experimentalists working in biological laboratories to devize tests of its relevance to their work. The mechanism is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
181
0
1

Year Published

1997
1997
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 302 publications
(188 citation statements)
references
References 29 publications
6
181
0
1
Order By: Relevance
“…Experimental and theoretical studies of the ''radical pair mechanism'' over the last 30 years have given an extraordinary variety of information on the magnetic properties, kinetics, and dynamics of radicals and their reactions (reviewed in refs. [9][10][11][12][13]. This field of endeavor has come to be called ''spin chemistry.…”
mentioning
confidence: 99%
“…Experimental and theoretical studies of the ''radical pair mechanism'' over the last 30 years have given an extraordinary variety of information on the magnetic properties, kinetics, and dynamics of radicals and their reactions (reviewed in refs. [9][10][11][12][13]. This field of endeavor has come to be called ''spin chemistry.…”
mentioning
confidence: 99%
“…The first and most dramatic is DNA fragmentation, which was described by Brocklehurst 1996;McLauchlan 1981;and Wyllie 1980. When DNA from apoptotically dying cells was subjected to agarose gel electrophoresis, ladders with -200 bp repeats were observed, corresponding histone protection in the nucleosomes of native chromatin.…”
Section: The Unique Aspects Of Oocytesmentioning
confidence: 99%
“…Another possibility is EMF-inducing apoptosis is mediated through the production of free radicals. It is shown that EMF exposure may result in production of free radicals (Lucia et al 2004;Brocklehurst and McLauchlan 1996;Grundler et al 1992;Alexander 1954). It is also shown that addition of antioxidants, such as vitamine E reduces EMF-induced changes in vivo and in vitro (Mohammadnejad and Soleimani Rad 2010).…”
Section: The Unique Aspects Of Oocytesmentioning
confidence: 99%
“…Furthermore, an underlying mechanism for interaction of EMFs with biological systems remains obscure, though free radical involvement and radon daughter attraction have both been suggested (Brocklehurst and McLauchlan, 1996;Henshaw et al, 1996). Confirmation of epidemiological results with animal and cell culture studies is crucial, but results of some such studies have proved controversial with replication studies sometimes contradicting initial results (Goodman and Shirley-Henderson, Syrian hamster dermal cell immortalization is not enhanced by power line frequency electromagnetic field exposure 1991; Lacy-Hulbert et al, 1995;Saffer and Thurston, 1995).…”
mentioning
confidence: 98%